2022
DOI: 10.4314/sajg.v8i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Landscape metrics analysis of land use patterns and changes in suburban local government areas of Ibadan, Nigeria

Abstract: This study examined the spatiotemporal pattern of urban growth and magnitude of changes in selected Local Government Areas (LGAs) in the suburban area of Ibadan using remote sensing cum spatial metrics. Data for the study were obtained from administrative maps of the study area, population data and satellite imageries. All of these were complemented with ground validations using Global Positioning System (GPS) receiver. Periods of change analysis were divided into two epochs; 1986 to 2002 and 2002 to 2017. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Results of the growth and pattern of land use development in Ijebu Ode between 1986 and 2021 indicated that there has been continuous increase in the growth of the built-up area which was a by-product of reduction in vegetation and cultivated land classes. By implication, this denotes the prevalence of urban expansion in the area as earlier reported in some earlier studies which noted the existence of inverse relationship between the built-up and other LULC such as vegetation [31,32,49,53].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Results of the growth and pattern of land use development in Ijebu Ode between 1986 and 2021 indicated that there has been continuous increase in the growth of the built-up area which was a by-product of reduction in vegetation and cultivated land classes. By implication, this denotes the prevalence of urban expansion in the area as earlier reported in some earlier studies which noted the existence of inverse relationship between the built-up and other LULC such as vegetation [31,32,49,53].…”
Section: Discussionsupporting
confidence: 62%
“…Urban landscape fragmentation is usually the consequence of changes in landscape structure [18,19,27]. These changes are by-products of decreasing heterogeneity of landscape compositions and profound landscape fragmentation [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%